(untitled) (LACCEI, 2024)
Abstract– The article identifies the main research trends published and indexed on reverse logistics during the years 2017 and 2022. The state of the art defines the concepts of reverse logistics, the environmental conditions of supply, as well as the main logistics business practices. established for this business model. The methodology uses the systematic literature review technique, under the PRISMA model. It is concluded that the literature shows a special concern for the standardized processes of reverse logistics to mitigate environmental damage, the effects of value creation, the level of efficiency, the general logistics costs of its implementation, as well as its impact on the transformation of the traditional supply chain.